Integrasi Statistical Quality Control dan Failure Mode and Effect Analysis Dalam Menganalisis Defect Pada Proses Produksi - Sri Kaidah; Tosty Maylangi Sitorus; Hartami Dewi (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2024)
One of the companies that make tools for printing at one of the printing companies in Jakarta has a product in the form of Offset Roller Printing, where Offset Roller Printing is a mainstay product with the highest sales. The company promises a declining trend in the rejection rate in 2024, with the rejection rate not exceeding 2%. For that, an analysis of the cause of the problem will be carried out until a repair proposal is obtained by using an integrated method which is Statistical Quality Control (SQC) with Failure Mode Effect Analysis (FMEA). Based on the check sheet, it shows the total production in January - December 2023 of 5699. On the overall operational map, there is no point that is outside the upper or lower operational limits. From the results of the FMEA analysis, it can be seen that the highest RPN is the cover for the method factor with the first priority having an RPN value of 252 which means that the vulcanization temperature is not reached or the temperature of the maturity point is not reached. unable to. There is a need to renew the vulcanization recipe so that the rubber matures perfectly and avoids the occurrence of oblong or closed defects. In addition, improvement proposals as a form of evaluation results are given related to the operator's attention factor, operator's skill, various types of materials, working environment temperature, no machine control, comfortable work environment, hostap plastic setting.